Pemetaan Wilayah Terdampak Covid-19 di Kota Bengkulu - Warsa Sugandi Karman; Tegar Aldaka Fikri; Zairin Zairin; Muhammad Alfi; Mirna Yunita (Universitas Prof. Dr. Hazairin, S.H, 2023)
This study aims to determine the map of the spread of COVID-19 cases in the city of Bengkulu. This research was carried out in the Bengkulu City Health Service area. The research method used in this study uses quantitative descriptive research. Data collection techniques were carried out using documentation and interview methods. The population was taken from all people infected with COVID-19 from March 2020-March 2021. The data analysis technique used in this study was descriptive statistics and geographic information systems (GIS). Processing data on the number of patients infected with Covid-19 uses a frequency distribution table and a classification table to determine which area belongs to the low, medium zone; high and very high.